2016
DOI: 10.5458/jag.jag.jag-2015_022
|View full text |Cite
|
Sign up to set email alerts
|

Screening Method for Novel Rice Starch Mutant Lines Prepared by Introducing Gene Encoding Starch Synthase IIa and Granule-bound Starch Synthase I from Indica Cultivar into a Branching Enzyme IIb-Deficient Mutant Line

Abstract: Rice is a staple food for over half the world s population. 1) The standard rice consumed in Japan is steamed rice from japonica cultivars. Numerous good-tasting japonica cultivars with excellent agricultural traits have been developed at agricultural stations. The starch properties in japonica rice cultivars are quite different from those of indica rice cultivars. These differences are mainly explained by the single nucleotide polymorphisms (SNPs) in the starch synthase IIa and granule-bound starch synthase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…The SS activity staining (Fig. 1d) showed that mobility of SSI between ss2a L gbss1 L ISA1 (T65) and SS2a GBSS1 ISA1 (IR36) were different, which is in agreement with previous studies (Chen and Bao 2016;Itoh et al 2016;Crofts et al 2017). SS2a gbss1 L isa1 (#1305A) and ss2a L GBSS1 isa1 (#1305B) lines showed similar mobility of SSI to ss2a L gbss1 L ISA1 (T65), while SS2a GBSS1 isa1 (#1305C) showed similar mobility of SSI to SS2a GBSS1 ISA1 (IR36).…”
Section: Confirmation Of Genotype and Starch Biosynthetic Enzyme Activitiessupporting
confidence: 92%
See 1 more Smart Citation
“…The SS activity staining (Fig. 1d) showed that mobility of SSI between ss2a L gbss1 L ISA1 (T65) and SS2a GBSS1 ISA1 (IR36) were different, which is in agreement with previous studies (Chen and Bao 2016;Itoh et al 2016;Crofts et al 2017). SS2a gbss1 L isa1 (#1305A) and ss2a L GBSS1 isa1 (#1305B) lines showed similar mobility of SSI to ss2a L gbss1 L ISA1 (T65), while SS2a GBSS1 isa1 (#1305C) showed similar mobility of SSI to SS2a GBSS1 ISA1 (IR36).…”
Section: Confirmation Of Genotype and Starch Biosynthetic Enzyme Activitiessupporting
confidence: 92%
“…Activity bands of PUL were assigned according to Fujita et al 2009. The mobility of PUL were different between ss2a L gbss1 L ISA1 (T65) and SS2a GBSS1 ISA1 (IR36), and ss2a L GBSS1 isa1 (#1305B) lines showed similar mobility of PUL to either ss2a L gbss1 L ISA1 (T65) or SS2a GBSS1 ISA1 (IR36), which is in agreement with previous studies (Chen and Bao 2016;Itoh et al 2016;Crofts et al 2017). Pho1 elongates glucans using glucose-1-phospate as a substrate, but its activity can be detected in reverse direction on native-PAGE, which hydrolyzes α-1,4 linked glucans (Satoh et al 2008).…”
Section: Confirmation Of Genotype and Starch Biosynthetic Enzyme Activitiessupporting
confidence: 89%